2015
DOI: 10.1186/s12889-015-1590-z
|View full text |Cite
|
Sign up to set email alerts
|

Sequential dengue virus infections detected in active and passive surveillance programs in Thailand, 1994–2010

Abstract: BackgroundThe effect of prior dengue virus (DENV) exposure on subsequent heterologous infection can be beneficial or detrimental depending on many factors including timing of infection. We sought to evaluate this effect by examining a large database of DENV infections captured by both active and passive surveillance encompassing a wide clinical spectrum of disease.MethodsWe evaluated datasets from 17 years of hospital-based passive surveillance and nine years of cohort studies, including clinical and subclinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 34 publications
(34 reference statements)
2
48
0
2
Order By: Relevance
“…Despite limitations in our current understanding of dengue pathogenesis, key risk factors for the development of severe dengue disease have been identified in longitudinal epidemiological studies [1013]. These studies have shown that the most important risk factor for severe disease manifestation is a secondary heterologous dengue infection [10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite limitations in our current understanding of dengue pathogenesis, key risk factors for the development of severe dengue disease have been identified in longitudinal epidemiological studies [1013]. These studies have shown that the most important risk factor for severe disease manifestation is a secondary heterologous dengue infection [10].…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] Ante el riesgo incrementado de hospitalización por casos de dengue virológicamente confirmado en el grupo de vacunados en niños de nueve años o menores, los periodos de seguimiento posteriores a la aplicación de la vacuna deben extenderse.…”
Section: Salud Pública De México / Vol 58 No 1 Enero-febrero De 2016unclassified
“…Como describe el reciente reporte del Comité Asesor de Seguridad en Vacunas de la Organización Mundial de la Salud (OMS), 24 es imperativo contar con más evidencia sobre el papel de la serología negativa a dengue al momento de vacunar, asociado con este riesgo, con esta vacuna o con cualquier otro candidato futuro.…”
Section: Salud Pública De México / Vol 58 No 1 Enero-febrero De 2016unclassified
“…There are four antigenically distinct DENV serotypes, DENV1-4. Infection with one DENV serotype typically induces lifelong protection against homotypic infection and temporary protection against heterotypic infections [2]. Clinical presentation of DENV infection varies from asymptomatic infection to a non-specific febrile illness (Dengue fever, DF) and the more severe dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS).…”
Section: Introductionmentioning
confidence: 99%